Access to cationic polyhedral carboranes via dynamic cage surgery with N-heterocyclic carbenes - Jan Vrána; Josef Holub; Maksim A. Samsonov; Zdeňka Růžičková; Josef Cvačka; Michael L. McKee; Jindřich Fanfrlík; Drahomír Hnyk; Aleš Růžička (Nature Communications, 2021)
In comparison to their neutral or anionic counterparts, examples of cationic boron clusters remain scarce. Here, the authors prepare a variety of cationic polyhedral boranes by reacting closo-10-vertex carboranes with N-heterocyclic carbenes; the resulting open-cage cationic nido- arachno- or closo- derivatives are water soluble, which may enable unprecedented applications.